1997
DOI: 10.1111/j.1365-2222.1997.tb01254.x
|View full text |Cite
|
Sign up to set email alerts
|

Bronchoalveolar lavage findings suggest two different forms of childhood asthma

Abstract: SummaryBackground It seems plausible that children with atopy and persistent asthma symptoms will, like their adult counterparts, have chronic airways inflammation. However, many young children with no other atopic features have episodic wheezing that is triggered solely by viral respiratory infections. Little is known as to whether airways inflammation occurs in these two asthma patterns during relatively asymptomatic periods. Methods Using a non-bronchoscopic bronchoalveolar lavage (BAL) procedure on childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
196
0
7

Year Published

1999
1999
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(224 citation statements)
references
References 26 publications
21
196
0
7
Order By: Relevance
“…A different mechanism may be present in persistent wheezers, given their different prognoses. We (5,15,16) and others (17)(18)(19) have reported that children with persistent wheeze are more likely than transient early wheezers to have high serum IgE levels, eosinophilia, and skin test reactivity to local aeroallergens. Lowe and coworkers (20) showed that, regardless of the development of early respiratory symptoms, children with a strong family history of asthma who had become sensitized to local allergens had significantly lower specific airway conductance at age 3 yr compared with nonsensitized children.…”
Section: Discussionmentioning
confidence: 99%
“…A different mechanism may be present in persistent wheezers, given their different prognoses. We (5,15,16) and others (17)(18)(19) have reported that children with persistent wheeze are more likely than transient early wheezers to have high serum IgE levels, eosinophilia, and skin test reactivity to local aeroallergens. Lowe and coworkers (20) showed that, regardless of the development of early respiratory symptoms, children with a strong family history of asthma who had become sensitized to local allergens had significantly lower specific airway conductance at age 3 yr compared with nonsensitized children.…”
Section: Discussionmentioning
confidence: 99%
“…27 In a study using blind bronchoalveolar lavage at the time of routine paediatric surgery, there were no eosinophils in the lavage of children with VAW, quite different from atopic asthmatics. 28,29 One is forced to the conclusion that VAW is nothing to do with eosinophilic inflammation, and should not be treated the same way.…”
Section: What Causes Vaw?mentioning
confidence: 99%
“…Children with chronic cough, without wheeze, due to cough variant asthma should exhibit airway inflammation similar to known atopic asthmatics, who have increased eosinophils and mast cells in their bronchoalveolar lavage fluid (BAL) [11] and increased concentrations of eosinophil cationic protein (ECP) and histamine in BAL [12]. The aim of the present study was to investigate the cell composition and inflammatory mediators within the airways of children with chronic cough and compare the results with the population of normal nonatopic children and atopic asthmatics, who had undergone lavage for both this and previous studies.…”
mentioning
confidence: 99%